Preventing Sexual Violence Against Students Through Structural Policy Interventions of Justice and Gender Equality (JED (Jurnal Etika Demokrasi), 2023)
The main problem in this research is the widespread violence and sexual harassment against students in Indonesian universities. The aim of this research is to analyze efforts to prevent sexual violence against students through the intervention of lecturers at universities in Indonesia. This research uses mixed research methods. Research informants, qualitative research using purposive sampling amounted to 30 people, while determining the research sample using random sampling techniques totaling 300 respondents. The data collection techniques used were questionnaires, observation, interviews and documentation. Qualitative data analysis was carried out through the stages of data reduction, data display and drawing conclusions, while quantitative data analysis used questionnaire verification, tabulation of questionnaire data and percentage of questionnaire data. The validity of qualitative data uses source triangulation and method triangulation, while quantitative data uses reliability tests (accuracy) and validation tests (correctness). The results of the research show that lecturer actor intervention was carried out by discussing human rights issues, power relations, disability perspectives, anti-gender-based violence, socializing the task force for preventing and dealing with sexual violence and implementing healthy relationships with students. Lecturer actor intervention can prevent sexual violence against students.